Expression of osteoprotegerin (OPG), TNF related apoptosis inducing ligand (TRAIL), and receptor activator of nuclear factor κB ligand (RANKL) in human breast tumours. Issue 1 (4th January 2006) - Van Poznak, C; Cross, S S; Saggese, M; Hudis, C; Panageas, K S; Norton, L; Coleman, R E; Holen, I
Abstract : Background: Osteoprotegerin (OPG) is involved in the regulation of bone turnover through binding to the receptor activator of nuclear factor κB ligand (RANKL), and has also been reported to be a potential survival factor for several different cell types. The survival effects are mediated through inhibition of the activity of tumour necrosis factor related apoptosis inducing ligand (TRAIL). Both breast and prostate cancer cells produce sufficient amounts of OPG to be protected against the effects of TRAIL in vitro. Aims: To investigate the spatial expression of OPG, RANKL, and TRAIL in non-neoplastic breast tissue and breast cancer, and its relation with oestrogen receptor (ER) expression. Methods: Forty breast cancers (20 ER+, 20 ER−) and five non-neoplastic breast tissue samples were stained with antibodies against OPG, RANKL, and TRAIL. Results: OPG was not expressed in non-neoplastic breast tissue except when colocalised with altered columnar epithelium. RANKL was expressed at the apical surface of luminal epithelial cells and TRAIL was expressed in myoepithelial cells. All three proteins were expressed in some breast cancers but showed no significant association with tumour type. OPG expression showed a significant positive correlation with ER expression (p = 0.011). Conclusions: This is the first published study of the spatial expression of OPG, RANKL, and TRAIL in breast tissue and breast cancer. The localisation of each protein was specific and they were not colocalised. This specificity may provide a useful marker of functional differentiation in breast cancer; for example, TRAIL expression as a marker of myoepithelial differentiation.